1991
DOI: 10.1111/j.1600-079x.1991.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of melatonin induces changes in porphyrins and in the histology of male and female hamster Harderian gland: Interrelation with the gonadal status

Abstract: In this paper, we have investigated the influence of melatonin on the histology and porphyrin content of the Syrian hamster Harderian glands. Daily afternoon injections of 25 micrograms of melatonin to female hamsters for 12 weeks resulted in the discontinuity of estrous cyclicity, a marked decrease in the Harderian gland intraluminal area occupied by porphyrins, and in a significant rise in the number of Type II cells. A similar decrease in porphyrins was observed after 8 weeks of ovariectomy. However, if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In all previous studies, type II cells were low in HGs of untreated wild-type females and inversely correlated with porphyrin accumulation. Never had such a considerable percentage of type II cells been found in normal females [Rodrõ Âguez-Colunga et al, 1991Mene Ândez-Pela  ez et al, 1992]. Only treatments affecting gonadosteroids, leading to virilization, caused rises in type II cells, though in conjunction with decreases in porphyrins; therefore, induced interconversions between feminine and masculine phenotypes always maintained this inverse correlation [Payne et al, 1977;McMasters and Hoffmann, 1984;Payne, 1994].…”
Section: Discussionmentioning
confidence: 95%
“…In all previous studies, type II cells were low in HGs of untreated wild-type females and inversely correlated with porphyrin accumulation. Never had such a considerable percentage of type II cells been found in normal females [Rodrõ Âguez-Colunga et al, 1991Mene Ândez-Pela  ez et al, 1992]. Only treatments affecting gonadosteroids, leading to virilization, caused rises in type II cells, though in conjunction with decreases in porphyrins; therefore, induced interconversions between feminine and masculine phenotypes always maintained this inverse correlation [Payne et al, 1977;McMasters and Hoffmann, 1984;Payne, 1994].…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that melatonin produced by type I cells probably acts on type II cells (paracrine effect of melatonin). Exogenous melatonin administration has been demonstrated to reduce the area occupied by intraluminal porphyrin accretions (Rodriguez-Colunga et al 1991) and the expression of the aminolevulinate synthase (the rate-limiting enzyme for porphyrin synthesis) gene and leads to decrease porphyrin concentrations (Dubey and Haldar 1997) in the rodent Harderian gland. Recently, Princ et al (1998) and Carneiro and Reiter (1998) have shown that, in the brain, melatonin prevents the damage induced by free radicals generated by porphyrin metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Lighting conditions clearly influence the effects of androgens on porphyrin concentrations and HG morphology (Clabough and Norvell, 1973;Formgren and Wetterberg, 1976;Van Jaarsveld et al, 1989;Weterberg, 1972). Melatonin has been found to decrease porphyrin concentration and porphyrin deposits in the HG and serum levels of thyroid hormones in the female Syrian hamster (Hoffman et al, 1989~;Rodriguez-Colunga et al, 1991). Also, Menendez-Pelaez et al (1993) demonstrated the presence of melatonin binding sites in the HG of Syrian hamsters.…”
Section: Introductionmentioning
confidence: 92%